Penanganan Moral Hazard di Lingkungan Direktorat Jenderal sebagai Upaya Optimalisasi Penerimaan Pajak - Yuliansyah, Izma Widya; Ludigdo, Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2008)
This research has a purpose to explore alternatives solution to solve moral hazard at Directorate General of Tax's area. Directorate General of Tax decide Fiscal Policy to collect and organize the taxes at its region but they facing many constraint, the one is moral hazard by Tax Officer and Tax Payer The results of this research has show that the moral hazard depend on internal control system that implemented at tax office, integrity and ethical behaviour of Tax Officer, tax regulation, tax system and also the society’s tax comprehension. Moral hazard at Tax Office has divide into 5 manners, there are personality section, data collection, services payment of Tax Payer, tax negotiation, and SPT’ manipulation. Moral hazard decrease the society’s trust to the Tax Officer and it made Tax Officer has a bad reputation to the society. Bad reputation of Tax Officer to the society influence the desire of Tax Payer to fulfill their duty with the results is the budget of tax revenues is hard to be completed. Alternative solutions to handle the moral hazard at Tax Office are by using ethical approaches in order to repair the Tax Officer behaviour, reduce and close the grey area in tax regulation, renew tax system, and also increase society’s comprehension on tax. Keywords: Directorate General of Tax, Moral Hazards, and Alternative Solutions.